2023
DOI: 10.3390/plants12203561
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Climate Changes on Geographic Distribution of Primula filchnerae, an Endangered Herb in China

Xin Jiang,
Wan-Jing Liu,
Yan-Zhao Zhu
et al.

Abstract: Primula filchnerae, an endangered plant endemic to China, has drawn people’s attention in recent years due to its ornamental value in flower. It was rarely recorded since being described in 1902, but it was rediscovered in 2009 and is now known from a limited number of sites located in Hubei and Shaanxi Provinces. Since the species is still poorly known, a number of unanswered questions arise related to it: How has P. filchnerae responded to past climate change and how might it respond in the future? Why was P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Some other studies also showed that the geological and climatic changes have profoundly affected the geographic distributions and species shifts in the Qinling Mountains and adjacent areas. For example, Jiang et al ( 2023) used species distribution modeling to investigate the geographic range changes of an endangered herb Primula filchnerae R. Knuth in the Qinling Mountains, and they found that the species range would migrate to the north of China in the future climatic scenario [48]. Meanwhile, Zhao et al (2023) detected the geographic changes of a shrub species Bashania fargesii (E. G. Camus) P. C. Keng and T. P. Yi in the Qinling Mountains, and the authors have also concluded that the species would migrate to the north of China in the future [49].…”
Section: Population Dynamics Changesmentioning
confidence: 99%
“…Some other studies also showed that the geological and climatic changes have profoundly affected the geographic distributions and species shifts in the Qinling Mountains and adjacent areas. For example, Jiang et al ( 2023) used species distribution modeling to investigate the geographic range changes of an endangered herb Primula filchnerae R. Knuth in the Qinling Mountains, and they found that the species range would migrate to the north of China in the future climatic scenario [48]. Meanwhile, Zhao et al (2023) detected the geographic changes of a shrub species Bashania fargesii (E. G. Camus) P. C. Keng and T. P. Yi in the Qinling Mountains, and the authors have also concluded that the species would migrate to the north of China in the future [49].…”
Section: Population Dynamics Changesmentioning
confidence: 99%
“…It is highly favored for its efficiency and accuracy, as it integrates limited species presence data with environmental information to effectively Plants 2024, 13, 1744 2 of 15 understand species distribution patterns and explore their relationships with environmental variables. The MaxEnt model is now widely used to study the impact of climate change on species distribution [9,10], such as Osmanthus fragrans [11], Cotoneaster multi florus [12], and Primula filchnerae [13]. The findings from these studies provide valuable guidance for the conservation of genetic diversity and the management of germplasm resources [14,15], and have further heightened public concern about climate change [16].…”
Section: Introductionmentioning
confidence: 99%